You know what I think that other guy is really foul so I will answer your question for da brainliest
Step 1: (( 18 * (x^3)) + 5x^2) - 2x
Step 2: what you need to do is figure out what this equation really means but here I will tell you
The real step 1 is multiply the coefficient of the first term by the constant 18 times negative 2= negative 36
Step 2: find two factors of negative 36 whose sum is equals the coefficient of the middle term, which is 5.
-36 + 1 = -35
-18 + 2 = -16
-12 + 3 = -9
-9 + 4 = -5
-6 + 6 = 0
-4 + 9 = 5 that’s it
So your answer will be x times (9x - 2) times ( 2x + 1)
That is your answer
Hope this helped